New molecular targets in non clear renal cell carcinoma: An overview of ongoing clinical trials. Issue 7 (July 2015) - Ciccarese, Chiara; Massari, Francesco; Santoni, Matteo; Heng, Daniel Y.C.; Sotte, Valeria; Brunelli, Matteo; Conti, Alessandro; Cheng, Liang; Lopez-Beltran, Antonio; Scarpelli, Marina; Cascinu, Stefano; Tortora, Giampaolo; et al.
<x xml:space="preserve">Abstract</x> Highlights nccRCC subtypes differ for their biological and clinical behavior. VEGF/VEGFR, mTOR and MET signaling pathways play a prominent role in nccRCC. The efficacy of anti PD-1/PDL-1 approaches should be tested in nccRCC patients. Understanding the molecular landscape of nccRCC is crucial for future therapies.